Alamandine and Its Receptor MrgD Pair Up to Join the Protective Arm of the Renin-Angiotensin System - Schleifenbaum, Johanna (Frontiers in Medicine, 2019)
Only a few years ago, alamandine was found to be a member of the protective arm of the renin-angiotensin system. It turned out to be an endogenous ligand of the G protein-coupled receptor MrgD. So far, MrgD had predominantly been studied in a neuronal context. The expression of the receptor in non-neuronal tissue showed hitherto unknown effects mediated by MrgD, most strikingly alamandine-induced vasodilation. Alamandine being a part of the non-classical renin-angiotensin system, a protective role of receptor activation seemed natural. This review summarizes the different effects of MrgD activation by alamandine in vasculature, in the central nervous system, and in organs as kidney and heart. Alamandine and MrgD are promising novel drug targets to protect the kidney and heart through anti-hypertensive actions.